Effect of various flow field designs and varying compression of electrode on the overall performance of the 100 cm² cell stack - Chan, Nicholas Zhen Zhong (Nanyang Technological University, 2023)
The shift towards sustainable sources of energy, has led many to turn to renewable forms of energy. Due to the instability generating this form energy, has led to a rise in the importance of energy storage. Vanadium Redox Flow Battery (VRFB) has always been an option for energy storage. Vanadium ions can exist four different oxidation state when mixed in sulfuric acid is able to effectively generate and store energy. VRFB simple working principle, versatility in size of different system, the stability it provides in its long service lifespan and the low maintenance needed for it to function has make it a popular form of Energy Storage System. Bipolar flow field design has always been an area where a lot of research are performed. It dictates the flow of the electrolyte in the system the distribution of the electrolyte that directly impacts the performance of the battery. From the very first bipolar there is no ribs or channel to the newest introduction of Interdigitated Flow Field with pins, different approaches have been pursed to in search improve the battery efficiency and reduce losses during the charging and discharging of the system. Electrode size and compression has always limted the reduction of the of the overall cell stack sizes. Properties such as contact surface of the electrode with the membrane and bipolar plate and compression of the of the felt is contradicts with the properties such as the porosity of the carbon felt that affects the ability to for effective transport of reactive spiece in the electrode. This Final Year Project seeks to investigate the various bipolar flow field design to determine their characteristic and also estabilish a relationship between the compression of the felt and the conductivty of the electrode. From the cell cycling, we identified that Serpentine flow field shows the best performance out of the flow field that was tested. It has shown the highest VE and EE while maintaining the high stability in the CE. From dry cell resistance test, we concluded with a higher compression, a higher conductivity of the cell is observed. However, this is not conclusive as factors such as flow of electroylte and effective surface area for kinectic is not accounted for. Lastly, different AEM and CEM were tested through cell cycling . CEM was seen to be better in terms of ion conductivity, EE and VE. With Yunji energy technology J114, performed well in terms of CE as well.